EFFECT OF NITROGEN FERTILIZATION ON GROWTH CHARCTERESTIC AND HAY YILD OF BARLEY VARITES - Lekaa Ali; Abbas AL-Hasan (Mesopotamia Journal of Agriculture, 2012)
A Field experiment was carried out in the growing seasons (2009-2010) and (2010-2011) at the experimental Station of College of Agriculture and Forestry, Mosul University, to study the effect of Nitrogen Fertilizer Levels, zero, 80 and 120 Kg N/ha as one dose and split applications on growth characteristics and Hay yield of Barley Cultivars namely; Fourat, Zanbaga , Aswed Arbai and two-rowed local black’.The experiment was applied by Using Split –Plot in Randomized Completely Block Design with three replicates. Nitrogen Fertilization have no clear effect on growth characters and hay yield in the first growing season due to the low rainfall and its irregular distribution, this was true for the one dose and split application of the fertilizer, with positive and negative response, while in the second season the Fertilizer levels were positively affected on flag leaf area, relative growth rate, fresh and dry yield of forage, which their valule at the Fertilizer level 80 Kg N/ha as one dose was superior over their values at control treatment by 26%, 3.6%, 27.9% and 33.3% respectively. Splitting Nitrogen level 80Kg N/ha caused increase in relative growth rate in the First season , and increase flag leaf area, fresh and dry forage yield in the second season. While splitting Fertilizer level 120 Kg N/ha increased the flag leaf area, fresh and dry forage yield in both growing seasons. In the first growing season, the local black variety was superior in all growth characters and hay yield with the exception of Flag leaf area, while in the second growing season the variety Zanbaga was surpassed over other varieties in most growth characters and hay yield